Historical Mob Violence and the 2016 Presidential Election. (March 2021) - Abbott, Rebecca; Bailey, Amy Kate
As a 2016 presidential candidate, Donald J. Trump invoked racially charged rhetoric to galvanize conservative white voters who felt left behind in the "new economy." In this article, we ask whether Trump's ability to attract electoral support in that way was linked to local histories of racist mob violence. We use county-level data on threatened and completed lynchings of Black people to predict support for Trump in the 2016 Republican presidential primary and general election across eleven southern states. We find that fewer voters cast their ballots for Trump in counties that had suppressed a comparatively larger share of potentially lethal episodes of racist mob violence. Supplementary analyses suggest that counties' histories of violence are also related to their electoral support for Republican presidential candidates more broadly. We posit that this correlation points to the durable effects of racist violence on local cultures and the imprint of community histories on the social environment.